Numerical and Experimental Study the Effect of Solid Particles Flow on Heat Pipe Performance - Hassan Al-Ghazali, Hafidh; Wahhab. Aljibory, Mohammed; Habeeb Alkharasani, Taher (International Journal of Engineering and Technology, 2018)
A numerical work supported by experimental results was carried out to studying of passing a hot solid particle on heat pipe performance. used Ansys fluent 18.0 as a computer program, geometry was published using design modular engaged in it. 3Dimention model with the steady state was studied to knowing the temperature distributed inside the evaporator and condenser part domain, more clearly to particle behavior and streamline 2Dimention model with transient was studied also. Depended on particle of 105µm diameter and experimental measuring properties set with height range (2.5 to 5) cm inside evaporator part from box, velocity with range (0.8739 to 1.377) m/s was take in consideration, the result shown enhancement in Nusselt number by (58) % when the velocity 1.377 m/s and particle bed height 5 cm compared with the first state, pressure drop with acceptable range was measured not exceed (42) %